(untitled) (The Research of Medical Science Review, 2025)
Objective: To determine the association between RDW to Albumin ratio and prognosis of acute coronary syndrome (ACS) in form of all-cause Mortality in patients admitted in ICU, CCU or Medicine Department. Study Design: Prospective Cohort Study. Study Setting: The Study was planned at Department of Internal Medicine and Cardiac Care Unit (CCU), Recep Tayyip Erdogan Indus Hospital, Muzaffargarh. Study Duration: From September’2024 to Febuary’2025. Methodology: This study enrolled 126 patients using non-probability consecutive sampling, categorized into high RAR (≥3.5) and low RAR (<3.5) groups. Demographics, clinical data, RDW, and albumin levels were recorded at admission. Patients were followed for 90-day all-cause mortality. Results: Mean age was 52.29 ± 19.64 years, and 57.9% were male. The 90-day mortality rate was 12.7%. Mortality was significantly higher in the high RAR group (19.0%) versus the low RAR group (6.3%) with RR = 3.471 (p = 0.032). Subgroup analysis showed higher mortality among older patients, females, diabetics, hypertensives, and those with a positive family history of ischemic heart disease(IHD). Conclusion: High RAR is a significant, low-cost biomarker associated with increased short-term mortality in ACS patients. It may serve as an early prognostic indicator to improve risk stratification and guide targeted interventions.